The effect of air quality on welfare accounting - Almut Balleer; Morten Endrikat (Philipps-University Marburg, School of Business and Economics, 2018)
For several decades, there has been a discussion in economics on how to appropriately measure economic welfare. Although it is common perception that a simple GDP evaluation bears several shortcomings, GDP per capita is still the most prominent measure of countries' welfare and of its development over time. In a recent paper, Jones and Klenow (2016) extend the huge existing literature on alternative welfare measures by a concept that is based on a utility framework and that incorporates, besides consumption, also life expectancy, inequality, and leisure. In this paper, we add a component of environmental quality, in particular air pollution, to this framework and show that for some country groups accounting for air quality remarkably changes their relative welfare position, both in terms of levels and growth rates over time. Especially for some emerging countries we find strong welfare reductions due to high levels of air pollution. Nevertheless, on average, our welfare measure is still highly correlated with GDP per capita. Our results highlight the importance of environmental aspects in welfare accounting.
Keywords: D63; I12; O54; O57; Q53; Q56; 330; Economic Welfare; Economic Development; Air Pollution; Environmental Economics